The 4 disciplines of execution : achieving your wildly important goals - McChesney, Chris; Covey, Sean.; Huling, Jim. (New York : Free Press, 2012)
Do you remember the last major initiative you watched die in your organization? Did it go down with a loud crash? Or was it slowly and quietly suffocated by other competing priorities? By the time it finally disappeared, it's likely no one even noticed. What happened? The "whirlwind" of urgent activity required to keep things running day-to-day devoured all the time and energy you needed to invest in executing your strategy for tomorrow! The 4 Disciplines of Execution can change all that forever. The 4 Disciplines of Execution (4DX) is a simple, repeatable, and proven formula for executing on your most important strategic priorities in the midst of the whirlwind. By following The 4 Disciplines -- Focusing on the Wildly Important; Acting on Lead Measures; Keeping a Compelling Scoreboard; and Creating a Cadence of Accountability -- leaders can produce breakthrough results, even when executing the strategy requires a significant change in behavior from their teams. 4DX is not theory. It is a proven set of practices that have been tested and refined by hundreds of organizations and thousands of teams over many years. When a company or an individual adheres to these disciplines, they achieve superb results--regardless of the goal. 4DX represents a new way of thinking and working that is essential to thriving in today's competitive climate. Simply put, this is one book that no business leader can afford to miss.
Pt. 1. The 4 disciplines of execution. Discipline 1: focus on the wildly important ; Discipline 2: act on the lead measures ; Discipline 3: keep a compelling scoreboard ; Discipline 4: create a cadence of accountability -- pt. 2. Installing 4DX with your team. What to expect ; Installing discipline 1: focus on the wildly important ; Installing discipline 2: act on the lead measures ; Installing discipline 3: keep a compelling scoreboard ; Installing discipline 4: create a cadence of accountability ; Automating 4DX -- pt. 3. Installing 4DX in your organization. Best practices from the best ; Focusing the organization on the wildly important ; Rolling out 4DX across the organization -- 4DX FAQ's -- Bringing it home -- So now what?
Includes bibliographical references and index.
Keywords: Goal setting in personnel management; Goal (Psychology); Organization